Effective micro-spray cooling for light-emitting diode with graphene nanoporous layers. (23rd March 2017) - Lay, Kok Keong; Cheong, Brian Mun Yew; Tong, Wei Li; Tan, Ming Kwang; Hung, Yew Mun
Abstract: A graphene nanoplatelet (GNP) coating is utilized as a functionalized surface in enhancing the evaporation rate of micro-spray cooling for light-emitting diodes (LEDs). In micro-spray cooling, water is atomized into micro-sized droplets to reduce the surface energy and to increase the surface area for evaporation. The GNP coating facilitates the effective filmwise evaporation through the attribute of fast water permeation. The oxygenated functional groups of GNPs provide the driving force that initiates the intercalation of water molecules through the carbon nanostructure. The water molecules slip through the frictionless passages between the hydrophobic carbon walls, resulting an effective filmwise evaporation. The enhancement of evaporation leads to an enormous temperature reduction of 61.3 °C. The performance of the LED is greatly enhanced: a maximum increase in illuminance of 25% and an extension of power rating from 9 W to 12 W can be achieved. With the application of GNP coating, the high-temperature region is eliminated while maintaining the LED surface temperature for optimal operation. This study paves the way for employing the effective hybrid spray–evaporation–nanostructure technique in the development of a compact, low-power-consumption cooling system.